First multipoint in situ observations of electron microbursts: Initial results from the NSF FIREBIRD II mission. Issue 6 (17th June 2016) - Crew, Alexander B.; Spence, Harlan E.; Blake, J. Bernard; Klumpar, David M.; Larsen, Brian A.; O'Brien, T. Paul; Driscoll, Shane; Handley, Matthew; Legere, Jason; Longworth, Stephen; Mashburn, Keith; Mosleh, Ehson; et al.
Abstract: We present initial dual spacecraft observations that for the first time both constrain the spatial scale size and provide spectral properties at medium energies of electron microbursts. We explore individual microburst events that occurred on 2 February 2015 using simultaneous observations made by the twin CubeSats which comprise the National Science Foundation (NSF) Focused Investigations of Relativistic Electron Bursts: Intensity, Range, and Dynamics (FIREBIRD II). During these microburst events, the two identically instrumented FIREBIRD II CubeSats were separated by as little as 11 km while traversing electron precipitation regions in low‐Earth orbit. These coincident microburst events map to size scales >120 km at the equator. Given the prevalence of coincident and noncoincident events we conclude that this is of the same order of magnitude as that of the spatial scale size of electron microburst, an unknown property that is critical for quantifying their overall role in radiation belt dynamics. Finally, we present measurements of electron microbursts showing that precipitation often occurs simultaneously across a broad energy range spanning 200 keV to 1 MeV, a new form of empirical evidence that provides additional insights into the physics of microburst generation mechanisms. Key Points: We present estimates of the size of individual microbursts from simultaneous observations of microbursts at 10 km spatial separation Microbursts can occur over the entire energy range for 200 keV to 1 MeV in energy simultaneously We present descriptions of the scientific capabilities of the FIREBIRD II CubeSat mission